HUBUNGAN MOTIVASI MAHASISWA PROGRAM SARJANA KEPERAWATAN DENGAN MINAT MELANJUTKAN STUDI PROFESI NERS DI PROGRAM STUDI ILMU KEPERAWATAN UNIVERSITAS SAM RATULANGI MANADO - Silaban, Reni Yatnasari; Bidjuni, Hendro; Hamel, Rivelino (JURNAL KEPERAWATAN, 2016)
Abstrack:Continuing education to a higher level would be the decision of eachstudent personally. Taking a decision must be made before making an action. The action is closely related to individual interests. Interest is a source of motivation for someone to do something. Motivation is one of the factors to enthuse someone for a purpose. Interests that absolutely must have a strong motivation and fundamental decisions that have been believed for the sake of the individual. Research Purpose: to identify the relationship of student motivation by interest in continuing to study professional nurses. Methods: the design of this research is analytic survey with cross sectional approach. The population in this study were 32 students in Nursing Science Program, University of Sam Ratulangi. The sampling technique using Simple Random Sampling. The study involved 32 students as respondents. The instrument used in this study were questionnaires motivation and interest questionnaires continue studies. Result: Analysis using Fisher's Exact Test and showed the p value 0.000 (P <0.05). Conclusion: there is a relationship between student motivation by interest in the profession nurses to continue their studies in Nursing Science Program UNSRAT Manado.Recommendation: an introduction of the study of professional nurses should be done since the beginning students attend undergraduate and entering nursing courses. Keyword : motivations, interests continue studies, professional nurses. Abstrak : Melanjutkan pendidikan ke jenjang yang lebih tinggi tentunya menjadi keputusan masing – masing pribadi mahasiswa. Mengambil keputusan harus dilakukan sebelum melakukan suatu sikap. Sikap berkaitan erat dengan minat individu. Minat merupakan sumber motivasi bagi seseorang untuk melakukan sesuatu. Motivasi menjadi salah satu faktor untuk menumbuhkan minat seseorang untuk suatu tujuan. Minat yang mutlak harus memiliki motivasi yang kuat dan mendasar demi keputusan yang sudah diyakini individu. Tujuan Penelitian: mengetahui hubungan motivasi mahasiswa dengan minat untuk melanjutkan studi profesi ners. Metode: desain penelitian ini adalah survey analitik dengan pendekatan cross sectional. Populasi pada penelitian ini adalah 32 mahasiswa di Program Studi Ilmu Keperawatan Universitas Sam Ratulangi Manado. Teknik pengambilan sampel menggunakan teknik Simple Random Sampling. Penelitian ini melibatkan 32 mahasiswa sebagai responden. Instrumen yang digunakan dalam penelitian ini yaitu kuesioner motivasi dan kuesioner minat melanjutkan studi. Hasil: analisis menggunakan Fishers ExactTest dan menunjukkan nilai p 0.000 (p<0.05). Simpulan: terdapat hubungan antara motivasi mahasiswa dengan minat melanjutkan studi profesi ners di Program Studi Ilmu Keperawatan UNSRAT Manado. Saran:pengenalan mengenai studi profesi ners sebaiknya di lakukan sejak awal mahasiswa mengikuti program sarjana dan memasuki program studi ilmu keperawatan. Kata Kunci : motivasi, minat melanjutkan studi, profesi ners.